PERAN LINGKUNGAN BELAJAR DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI LEMBAGA PENDIDIKAN PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO - Shofiyah , St.; Fu’adah, Shofwatul (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
Educational institutions are a learning environment that is a planned container that is believed to be able to change or shape children's character to be better than before with all their potential. The learning environment should be understood as an important factor in shaping the character of students after the family environtment. The thing that needs to be considered in the success of character education in schools is a conducive-academic environment.The school environment can affect the child's personality, and from the environment, students will learn and shape their character naturally.The result showed the things that affect to character formation in educational institution at Pondok Pesantren Salafiyah Syafi’iyah area conducive learning environment and then in its implementation exemplary models, habituation, and discipline from all parties so that there is a real role model for students how to give examples of real character in life.